Vitrectomy in the surgical treatment of rhegmatogenic retinal detachment from the position of immediate or delayed cataract phacoemulsification. Systematic review - A. S. Golovin; S. A. Sai; A. V. Malyshev; I. G. Ovechkin (Российский офтальмологический журнал)
The review is devoted to the problem of surgical treatment (based on vitrectomy, VE) of rhegmatogenous retinal detachment (RRD) from the position of performing/not performing one-stage cataract phacoemulsification. The literature analysis was performed using the RSCI and PubMed databases. The obtained results indicate approximately similar (88.7–100.0%) levels of probability of achieving anatomically complete retinal reattachment during phacovitrectomy (FVE) and during isolated vitrectomy (VE). Along with this, a tendency towards some myopization of the eye after FVE is noted compared to VE, which may be associated with the multifactorial nature (calculation formulas, IOL type) of the effect of FVE on postoperative refraction. In addition, the literature data show a similar nature and frequency of complications in the above surgical approaches to the treatment of RRD. At present, there are no clear recommendations whether VE without lens surgery should be performed first or whether combined FVE may be a better strategy. In the long term, it is necessary to note the development of alternative criteria for the safety and effectiveness of surgical intervention related to expert assessment of the fundus condition and determination of indications for FVE (stage of proliferative vitreoretinopathy, duration of the disease, localization of retinal breaks and proliferative process), as well as a study of the dynamics of the patient's “quality of life”.